Adaptive consensus problems of heterogeneous multi-agent systems with saturations. Issue 2 (25th January 2020) - Miao, Guoying; Cao, Jinde; Li, Tao; Zheng, Bo-Chao
Abstract : The paper discusses consensus problems of heterogeneous multi-agent systems with saturation constraints, which is made up of agents having the first- and second-order integrators. Based on distributed adaptive parameters design approaches, several consensus algorithms with saturations for multi-agent systems are given under the fixed topology. Moreover, corresponding communication protocols are designed under switching cases. Furthermore, adaptive centralised and distributed event-triggered conditions are introduced to reduce energy consumption of agents, respectively. By applying Lyapunov function method, models transformation techniques and graph theory, some sufficient consensus conditions are derived. Finally, simulation examples are offered to test proposed results.